2003
DOI: 10.1086/380206
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Genomewide Linkage Study in 353 Sib Pairs with Schizophrenia

Abstract: We undertook a genomewide linkage study in a total of 353 affected sib pairs (ASPs) with schizophrenia. Our sample consisted of 179 ASPs from the United Kingdom, 134 from Sweden, and 40 from the United States. We typed 372 microsatellite markers at approximately 10-cM intervals. Our strongest finding was a LOD score of 3.87 on chromosome 10q25.3-q26.3, with positive results being contributed by all three samples and a LOD-1 interval of 15 cM. This finding achieved genomewide significance (P<.05), on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 66 publications
6
89
0
Order By: Relevance
“…98 Evidence for linkage of 6q15, 12q24 and 20q12, but not for 6q24-22, 1q21-22, 13q32-34 and 8p12-22 was also reported. It is notable that the region 12q24 is a novel linkage locus; 99 yet the gene encoding DAO is located close to this area and appears to be a contributory factor to the illness through its interaction with DAOA.…”
Section: Chromosome Xmentioning
confidence: 98%
See 1 more Smart Citation
“…98 Evidence for linkage of 6q15, 12q24 and 20q12, but not for 6q24-22, 1q21-22, 13q32-34 and 8p12-22 was also reported. It is notable that the region 12q24 is a novel linkage locus; 99 yet the gene encoding DAO is located close to this area and appears to be a contributory factor to the illness through its interaction with DAOA.…”
Section: Chromosome Xmentioning
confidence: 98%
“…139 Novak reevaluated the results of her previous investigation, using a more accurate method, a larger set of matched samples, and found an upregulation of the isoform Nogo C in schizophrenia. 140 Convergent evidence for the role of the Nogo gene in schizophrenia also comes from 111 Mediates oligo-oligodendrite and oligo-neuron adhesion 111 Provides a trophic signal to oligodendrites, without which oligodendroglial deterioration occurs 101 Regulates the properties of sodium channels at the nodes of Ranvier 111 MAG protein binds to the Nogo-66 receptor and inhibits axonal growth in vitro 112 MAG-deficient mice show delayed myelination and hypomyelination, but the latter is not associated with a loss of oligodendrites 111 MAG-deficient mice demonstrate an age-dependent dysfunction in myelin 98,111 Downregulation of the MAG protein has been shown at anterior frontal cortex 113 2 MAL 2qcen-13 Is expressed only when myelin compaction occurs 111 Is localized close to structural proteins (MBP and PLP1) 111 It may have functional contact with myelin glycosphingolipids 114 Organizes and stabilizes myelin via adhesion 114 Transgenic mice with increased MAL gene dosage revealed alterations of axon-glia interaction 115 MAL-deficient mice show defects in the maintenance of multiple domains of myelinated CNS axons, indicating aberrant protein trafficking 115 MAL-deficient mice demonstrate major alterations on the structural level (e.g. aberrant inclusions of cytoplasm within compact CNS myelin).…”
Section: Oligodendrocyte-related Genes Associated With Schizophreniamentioning
confidence: 99%
“…30 Interest in the proximal region of chromosome 22q as harboring a susceptibility gene for schizophrenia has in part resulted from whole genome linkage scans. Although linkage has not been found in most such scans, proximal chromosome 22q has shown one of the stronger linkages to schizophrenia, [31][32][33][34][35][36][37] especially when considered in recent meta-analyses of schizophrenia genome scans using different methods. 38,39 There are also some linkages here in bipolar disorder studies [40][41][42][43] and meta-analytically.…”
mentioning
confidence: 99%
“…Suggestive evidence for linkage distal to F-4 was also demonstrated for a modifier gene in Huntington's disease. 54 The fifth focus (F-5) is at 162 Mb with the strongest evidence for linkage on 6q 29 in an SCZ pedigree. Although there are no other supporting linkage studies, altered levels have been shown in the hippocampus of schizophrenics for two proteins encoded by genes in this location (TCP1 and MnSOD).…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al 29 Bailer et al 28 same TRAR4 SNPs with SCZ in the sample that yielded a very significant LOD score at this location (Amann et al). 34 A pioneer work in proteomics has also pointed to the role of genes on chromosome 6q in SCZ.…”
Section: Schizophrenia Bipolar Othermentioning
confidence: 98%